2015
DOI: 10.1126/scisignal.aab3138
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomics reveals new roles for the protein phosphatase PP6 in mitotic cells

Abstract: Protein phosphorylation is an important regulatory mechanism controlling mitotic progression. Protein phosphatase 6 (PP6) is an essential enzyme with conserved roles in chromosome segregation and spindle assembly from yeast to humans. We applied a baculovirus-mediated gene silencing approach to deplete HeLa cells of the catalytic subunit of PP6 (PP6c) and analyzed changes in the phosphoproteome and proteome in mitotic cells by quantitative mass spectrometry–based proteomics. We identified 408 phosphopeptides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 103 publications
3
72
0
Order By: Relevance
“…HeLa cells were infected with either control or PP6c shRNA baculoviruses and synchronized in mitosis using Taxol. As previously shown (55, 56), Aurora A Thr 288 phosphorylation significantly increased upon reduction of PP6c protein abundance (Figure 6A). Conversely, Aurora A Thr 288 phosphorylation significantly decreased upon treatment with Plk1 inhibitor BI2536 (Figure 6A, column 3) and was abolished in the absence of PP6c, which suggests that Plk1’s effect on Aurora A Thr 288 phosphorylation is mediated by PP6c.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…HeLa cells were infected with either control or PP6c shRNA baculoviruses and synchronized in mitosis using Taxol. As previously shown (55, 56), Aurora A Thr 288 phosphorylation significantly increased upon reduction of PP6c protein abundance (Figure 6A). Conversely, Aurora A Thr 288 phosphorylation significantly decreased upon treatment with Plk1 inhibitor BI2536 (Figure 6A, column 3) and was abolished in the absence of PP6c, which suggests that Plk1’s effect on Aurora A Thr 288 phosphorylation is mediated by PP6c.…”
Section: Resultssupporting
confidence: 88%
“…Although early reports demonstrated protein phosphatase 1 (PP1c) as capable of dephosphorylating the T-loop of Aurora A in vitro (53, 54), more recent studies support a PP6 holoenzyme as the primary T-loop phosphatase for Aurora A in cells (55, 56). As introduced above, Aurora A is the activating kinase for Plk1 (13, 14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The constructs allowing expression of human PP1C ( PPP1CA ), PP5C ( PPP5C ) and PP6C ( PPP6C ) were created using standard cloning methods as previously described [22,24,26,27]. Expression and purification of PP5C were performed essentially as described previously [22].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a positive regulatory mode of condensin I is induced by mitosis-specific Cdc2-mediated phosphorylation [Kimura et al, 1998;Takemoto et al, 2004]. Studies on the phosphoproteome and proteome in mitotic cells by quantitative mass spectrometry-based proteomics revealed that dephosphorylation of CAP-G by protein phosphatase 6 is opposed to CK2-dependent phosphorylation and required for the proper chromosome condensation and segregation in anaphase [Rusin et al, 2015]. Recently, based on chromatin immunoprecipitation sequencing experiments, Sutani et al [2015] reported that fission yeast condensin is localized to centromeres, ribosomal DNA (rDNA), and unwound DNA on the chromosome arms in a transcription-dependent manner in mitosis.…”
Section: Condensin Is Concentrated At the Centromere Or Kinetochorementioning
confidence: 99%